Progress in treatment of pathological neuropathic pain after spinal cord injury - Li, Jian; Kang, Wenqing; Wang, Xi; Pan, Fang (Frontiers in Neurology, 2024)
Pathological neuropathic pain is a common complication following spinal cord injury. Due to its high incidence, prolonged duration, tenacity, and limited therapeutic efficacy, it has garnered increasing attention from both basic researchers and clinicians. The pathogenesis of neuropathic pain after spinal cord injury is multifaceted, involving factors such as structural and functional alterations of the central nervous system, pain signal transduction, and inflammatory effects, posing significant challenges to clinical management. Currently, drugs commonly employed in treating spinal cord injury induced neuropathic pain include analgesics, anticonvulsants, antidepressants, and antiepileptics. However, a subset of patients often experiences suboptimal therapeutic responses or severe adverse reactions. Therefore, emerging treatments are emphasizing a combination of pharmacological and non-pharmacological approaches to enhance neuropathic pain management. We provide a comprehensive review of past literature, which aims to aim both the mechanisms and clinical interventions for pathological neuropathic pain following spinal cord injury, offering novel insights for basic science research and clinical practice in spinal cord injury treatment.